Standar Nasional Pendidikan Dasar Dan Menengah - Alawiyah, Faridah (Jurnal Aspirasi, 2017)
Education is an important aspect in a nation development. However, the achievement of education in Indonesia currently has not yet reached the best quality of education. Various policies in an effort to improve the quality of education have been done by the government and is still an ongoing process. Implementation of education in Indonesia refers to eight standards compiled by the National Education Standards Agency (BSNP). The material of these standard has been contained in various government policies. However, in order to achieve goals of these standards are still encountered various problems such as the low quality of education. This article tries to describe in general the standardization of education, eight national standards of education, and various problems in the achievement of national education standards at the level of primary and secondary education. Education that meets the standards must be met based on various criteria that have been set forth in various laws and regulations. The results of this article established that the standard of education still faces various problems, especially on the components of graduate competency standards, inadequate standards of facilities and infrastructure, standard of educator and education personnel, and also the management of standards.Pendidikan merupakan aspek penting dalam pembangunan bangsa. Namun, pencapaian pendidikan di Indonesia saat ini belum mencapai kualitas pendidikan terbaik. Berbagai kebijakan dalam upaya meningkatkan kualitas pendidikan telah dilakukan oleh pemerintah dan masih terus berlanjut. Pelaksanaan pendidikan di Indonesia mengacu pada delapan standar yang disusun oleh Badan Standar Nasional Pendidikan (BSNP). Materi standar ini telah terkandung dalam berbagai kebijakan pemerintah. Namun, untuk mencapai tujuan standar ini masih ditemui berbagai masalah seperti rendahnya mutu pendidikan. Artikel ini mencoba untuk mendeskripsikan secara umum standardisasi pendidikan, delapan standar pendidikan nasional, dan berbagai masalah dalam pencapaian standar pendidikan nasional di tingkat pendidikan dasar dan menengah. Pendidikan yang memenuhi standar harus dipenuhi berdasarkan berbagai kriteria yang telah ditetapkan dalam berbagai peraturan perundangundangan. Dari hasil artikel ini diketahui bahwa standar pendidikan masih menghadapi berbagai masalah, terutama pada komponen standar kompetensi lulusan, standar sarana dan prasarana yang tidak mencukupi, standar pendidik dan tenaga kependidikan, serta pengelolaan standar